Sa mata ng mga bata a descriptive study on children ages five to eight years old's Youtube kids' platform engagement - Fonacier, Jerica Malliah B.; Tolentino-Canlas, Daphne-Tatiana . (Quezon City College of Mass Communication, University of the Philippines, 2023)
Since its release in 2015, YouTube Kids, a video streaming application specifically designed for children, has already gained traction in different parts of the world. This study examined the experiences of children ages five to eight years old (preschool to school age) in using the YouTube Kids application along with its many features. The researcher observed and interviewed five children to better understand how they perceive and make sense of their platform engagement. Using a phenomenological framework, this study described the children's experience and understanding of the platform, specifically how they make sense of video streaming platforms like YouTube Kids. Data analysis from the field notes and dialogue with the participants revealed six key themes: provides entertainment, autonomy and sense of control, YouTube Kids as their playground, fosters fun while learning, and development of technical skills. Recommendations for future researchers include taking different approaches in studying children and digital media, and even including parents as part of this kind of study.

Keywords: children, YouTube Kids, phenomenology, screen media
Mula nang ilabas ito taong 2015, ang Youtube Kids, isang video streaming application na partikular na idinisenyo pare as mga bata, ay nakakuha na ng traksyon sa iba't ibang bahagi ng mundo. Ang pag-aaral na ito ay tumuon sa mga karanasan ng mga batang edad lima hanggang walong taong gulang. (preschool hanggang school age) sa paggamit ng Youtube Kids application at ang maraming features nito. Ang mananaliksik ay nagmasid at nakipagkwentuhan sa limang magkakaibang mga bata sa pagtatangkang maunawaan kung paano nila naiintindihan at nararanasan ang kanilang pakikipag-ugnayan sa plataporma. Gamit ang penomenolohiya, ilalarawan ng pag-aaral na ito ang pag-unawa at karananasan ng mga bata sa Youtube KIds, partikular kung paano nila naiintindihan ang mga plataporma ng videostreaming katulad ng Youtube Kids. Ang pagsusuri ng mga datos mula sa mga filed notes at pakikipag usap sa mga kalahok ay nagsiwalat ng limang pangunahing tema: nagbibigay ng libangan. awtonomiya at pakiramdam ng kontrol, ang YouTube Kids bilang kanilang palarua, nagpapaunlad ng kasiyahan habang nag-aaral, at pagpapaunlad ng mga teknikal na kasasayan. Kasama sa mga rekomendasyon pars sa mga susunod na mananaliksik ang pagkuha ng iba't ibang diskarte sa pag-aaral ng mga bata at digital media, at maging ang pagsasama ng mga magulang bilang bahagi ng ganitong uri ng pag-aaral

Mga Susing Salita: mga bata, YouTube Kids, penomenolohiya, screen media
Vita.
Thesis
Includes bibliographical references (pages 55-65) and appendices (pages 66-132)
Keywords: Streaming video -- Children; Social media -- Children